Fodor's Maine coast 2023 - Collins, Andrew; Hall, Alexandra; Quigley, Annie P.; Rudalevige, Christine Burns; Ruoff, Mary; Steadman, Mimi (Fodor's Travel, 2023)
"Whether you want to eat lobster, sail on a windjammer, or hike Cadillac Mountain, the local Fodor's travel experts in Maine are here to help! Fodor's Maine Coast: with Acadia National Park guidebook is packed with maps, carefully curated recommendations, and everything else you need to simplify your trip-planning process and make the most of your time. This brand new title has been designed with an easy-to-read layout, fresh information, and beautiful color photos."--